Profile of T cells after dexamethasone treatment in BABL/c mice - Januarisasi, Iga Dwi (Biotropika: Journal of Tropical Biology, 2015)
ABSTRACT Regulation of homeostatic mechanisms and the development of T lymphocytes is influenced by several things, one of them is glucocorticoids. Dexamethasone is a synthetic glucocorticoid drugs used in the treatment for several diseases acted as an anti-inflammatory. The aim of this experiment was to confirm the effect of dexamethasone at normal dose and high dose on T cell profile and also to know the quantity of T cells after dexamethasone injection in each dose. This experiment we applied 18 mice in the age of 2 week and divided into 3 treatment groups with six replication i.e. control, dexamethasone injection with normal dose (0.5 mg/kg BW) and high dose (10 mg/kg BW), then observed on day-7 after injection. T cells were isolated from the spleen and analyzed by flow cytometry. Data analysis was confirmed with the ANOVA test followed by Turkey test with significance different (Î±) of 0.05. The result showed that dexamethasone act as immunosuppressant agent on high dose (10 mg/kgBB). Dexamethasone injection with normal dose on healthy mice showed no significant different in total number of CD4+, CD8+, CD4+CD62L, and CD8+CD62L compared to control. But, dexamethasone injections with high dose showed that the total number of CD4+, CD8+, CD4+CD62L, and CD8+CD62L were decreased significantly. Key words: Dexamethasone, Flowcyto metry, Glucocorticoid, Immunosuppressant, T lymphocyte.